Echoes of Francysk Skaryna’s Editions in Western Europe: Teseo Ambrogio, Pietro Paolo Vergerio and Jacques Lelong - Shutova, Olga (Senoji Lietuvos literatūra, 2024)
The article examines works of West European scholars containing references and quotations from Skaryna’s editions in the context of their epoch. The analysis of this very context lets us trace the circumstances and connections of Skaryna’s appearance in West European literature from the early 16th to the early 18th century. An intellectual history approach allows us to reconsider the citing of Skaryna’s editions in the work of the Italian linguist Teseo Ambrogio degli Albonesi, where we can presuppose the presence of multiple transliterated quotations from the books of Skaryna’s Bible. Clarification of the sources of citations, their filiation, and the history of editions, reveals the necessity to reinterpret sources such as Pietro Paolo Vergerio’s testimony (and subsequently of the French bibliographer Jacques Lelong) on the role of Skaryna’s Ruthenian edition, and the unity of all Slavic biblical translations, and to assess Skaryna’s oeuvre for the dissemination of Knowledge by Szymon Starowolski.
Keywords: Francysk Skaryna; Bivlia ruska; Teseo Ambrogio degli Albonesi (Theseus Ambrosius ex Comitibus Albonesii); biblical translations; Pietro Paolo Vergerio; Szymon Starowolski